Ecology, Nature and the Human in Edwin Thumbooâ€™s Poetry - Sankaran, National University of Singapore, Chitra (Asiatic: IIUM Journal of English Language and Literature, 2013)
In recent decades a growing concern for the environment and humansâ€™ relationship to it has prompted a group of literary critics, who have since been labelled ecocritics, to foregroundÂ placeÂ in literature as a new critical category. All ecological criticism shares the fundamental premise that human culture is connected to the physical world, affecting it and affected by it. Ecocriticism takes as its subject the interconnections between nature and culture, specifically the cultural artefacts of language and literature. Â  Â  This study attempts to make a case for Thumboo as an ecological poet. It discusses why Thumbooâ€™s treatment of the historical theme is distinctive, subversive, and even at times anathematic to progress-oriented national discourses. It will then examine ways in which his poems forge an â€œorganicâ€ synthesis with nature and conclude by discussing Thumbooâ€™s eco-critical leanings.